HbA1c as an Early Diagnostic Marker in Gestational Diabetes Mellitus: A Retrospective Study - Rukhsana Saboor, Fahad Aman Khan, Imran Khan, Amanullah Lail, Amanullah Bhutto, Ratan Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the efficacy of HbA1c as a single diagnostic marker of Gestational Diabetes mellitus (GDM). Study Design: A retrospective study Place and Duration: This study was conducted at Ghulam Muhammad Mahar Medical College Sukkur from June 2021 to June 2022 Methodology: In this retrospective study, a non-probability technique was used. The sample size is 19,065 pregnant women divided into two groups i.e. GDM and Non-GDM.(N=3458 in group 1 and N=15,608 in group 2). This study observes different parameters and tests to evaluate the efficiency of the HbA1c test for the diagnosis of GDM. Inclusion criteria included all pregnant females older than 18 years in their 1st trimester of pregnancy (at the end of 12 weeks of pregnancy). Results: The number of females suffering from GDM is about 3458(18.1%) of the sample size. The average level of HbA1c in female patients with GDM (Group 1) is approximately higher than in female patients with Non-GDM(Group2). HbA1c-thresholds in %were seen higher in older than 24 years of females. HbA1c is significantly higher in the GDM group than in the Non-GDM group. In a sample size of GDM patients aged 35-39 showed HbA1c levels, 62.4 sensitivity and 58.6% specificity at a cut-off value of 5.% (31 mmol/mol) for GDM diagnosis. Practical implication: Because of the high sensitivity and low specificity of HbA1c for the diagnosis of GDM in pregnant women, HbA1c may be a straightforward and less invasive screening test alternative for OGTT in GDM patients. Conclusion: HbA1c test provide assistance for the diagnosis of GDM but it is not used as a measured test to diagnose diabetes in pregnant women, it provides a measured diagnosis for diabetes mellitus type 1. Keywords: Gestational diabetes mellitus (GDM), HbA1c, Oral glucose tolerance test (OGTT), Diabetes mellitus type 2, Personalized Diabetes Management (PDM)